Persepsi Pengguna Jasa Calo Terhadap Upah (Ujrah) Calo Pembayaran Pajak Pada Kendaraan Bermotor (Studi Kasus Di Kecamatan Seruyan Hilir Kabupaten Seruyan) - Mariah Nia Alfiana, Siti; Mahmud, M.Ag, Dr. H. Hamdan (Sharia Journal and Education Center Publishing, 2024)
Abstract Perceptions of using broker services regarding brokers' wages (ujrah) in paying motor vehicle tax (PPKB). On the one hand, users of broker services say they are helped by the convenience and practicality provided by brokers, but on the other hand, users of broker services can be harmed by high wages (ujrah) of brokers, cost uncertainty, lack of transparency, and non-compliance with regulations. According to the perception of broker service users, brokers often offer assistance in managing PPKB in exchange for wages (ujrah) which are considered unreasonable, because they are not commensurate with the services provided. Apart from that, according to the perception of broker service users, brokers also often take advantage of broker service users' ignorance about the PPKB process for personal gain. As a result, various perceptions emerged among users of broker services in Seruyan Hilir District, Seruyan Regency regarding the wages (ujrah) they paid. This research is empirical legal research with a qualitative approach, using interview methods, the results of research conducted by broker service users in Seruyan Hilir District, Seruyan Regency who conveyed their perception that brokers' wages (ujrah) for their services in helping PPKB are a habit of broker service users who continuously continuous, caused by influencing factors, namely functional factors and structural factors and the reasons why the implementation of brokers' wages (ujrah) in paying motor vehicle tax in Seruyan Hilir District, Seruyan Regency is permissible or legal in terms of Islamic law Keywords : Broker service users, wages (Ujrah), motor vehicle tax payments Abstrak Persepsi penggunaa jasa calo terhadap upah (ujrah) calo pada pembayaran pajak kendaraan bermotor (PPKB). Di satu sisi, pengguna jasa calo mengatakan terbantu dengan kemudahan dan kepraktisan yang diberikan calo, namun di sisi lain pengguna jasa calo dapat dirugikan dengan upah (ujrah) calo yang tinggi, ketidakpastian biaya, kurangnya transparansi, dan ketidaksesuaian dengan peraturan. Menurut persepsi pengguna jasa calo, calo kerap menawarkan bantuan untuk mengurus PPKB dengan imbalan upah (ujrah) yang dianggap tidak wajar, karena tidak sepadan dengan pelayanan yang diberikan. Selain itu juga menurut persepsi pengguna jasa calo, calo juga sering kali memanfaatkan ketidaktahuan pengguna jasa calo tentang proses PPKB untuk keuntungan pribadi. Akibatnya, muncul beragam persepsi di antara pengguna jasa calo di Kecamatan Seruyan Hilir Kabupaten Seruyan terhadap upah (ujrah) yang mereka bayarkan. Penelitian ini merupakan penelitian hukum empiris dengan pendekatan kualitatif, menggunakan metode wawancara, hasil penelitian yang dilakukan oleh pengguna jasa calo di Kecamatan Seruyan Hilir Kabupaten Seruyan yang menyampaikan persepsinya menganggap upah (ujrah) calo atas jasanya membantu PPKB merupakan sebuah kebiasaan pengguna jasa calo yang terus-menerus, disebabkan oleh adanya faktor yang mempengaruhi, yakni faktor fungsional dan faktor struktual dan alasan pelaksanaan upah (ujrah) calo dalam pembayaran pajak kendaraan bermotor di Kecamatan Seruyan Hilir Kabupaten Seruyan dibolehkan atau sah dalam tinjauan hukum Islam Kata Kunci : Pengguna jasa calo, Upah (Ujrah), Pembayaran Pajak Kendaran Bermotor